Unearthing the Economic and Social Consequences of Earthquakes - Cevat Giray Aksoy; Maxim Chupilkin; Zsoka Koczan; Alexander Plekhanov (Institute of Labor Economics (IZA), 2024)
The purpose of this paper is to offer a comprehensive overview of the socio-economic effects of earthquakes. We begin with a thorough literature review. Following this, we assess policy measures taken in response to major earthquakes, drawing on existing research to formulate insights and recommendations that policymakers can use to effectively navigate the risks in the aftermath of such disasters. In addition to reviewing the literature and analyzing policy interventions, we conduct an in-depth examination of the economic repercussions of earthquakes. Our analysis utilizes data from around 80 significant earthquakes across more than 30 countries. The findings indicate that, while the overall effect of major earthquakes on GDP per capita is generally small, the impact on fiscal accounts can be substantial, although this varies significantly between economies. External trade balances tend to weaken, with a considerable decrease in exports and an ambiguous effect on imports.
Keywords: E60; H54; H84; Q54; 330; earthquake; synthetic controls; policy responses; Türkiye